2016
DOI: 10.1513/annalsats.201603-161oc
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged Dural Sac in Idiopathic Bronchiectasis Implicates Heritable Connective Tissue Gene Variants

Abstract: Rationale: Patients with idiopathic bronchiectasis are predominantly female and have an asthenic body morphotype and frequent nontuberculous mycobacterial respiratory infections. They also demonstrate phenotypic features (scoliosis, pectus deformity, mitral valve prolapse) that are commonly seen in individuals with heritable connective tissue disorders.Objectives: To determine whether lumbar dural sac size is increased in patients with idiopathic bronchiectasis as compared with control subjects, and to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…These patients have physical characteristics such as a tall, asthenic morphotype, scoliosis, pectus excavatum, mitral valve prolapse, and dural ectasia that overlap with heritable connective tissue disorders such as Marfan and Ehlers Danlos syndromes. 43, 44 Both bronchiectasis and pulmonary NTM infections have been noted in a well characterized population of these heritable connective tissue disorders. 45 Conversely, key characteristics such as bronchiectasis, NTM infection, and connective tissue disease features have been reported in a high proportion of 1 st and 2 nd degree relatives of carefully phenotyped idiopathic bronchiectasis patients with pulmonary NTM infections, strongly suggesting a genetic component to the disease.…”
Section: Endotypes and Genotypesmentioning
confidence: 99%
“…These patients have physical characteristics such as a tall, asthenic morphotype, scoliosis, pectus excavatum, mitral valve prolapse, and dural ectasia that overlap with heritable connective tissue disorders such as Marfan and Ehlers Danlos syndromes. 43, 44 Both bronchiectasis and pulmonary NTM infections have been noted in a well characterized population of these heritable connective tissue disorders. 45 Conversely, key characteristics such as bronchiectasis, NTM infection, and connective tissue disease features have been reported in a high proportion of 1 st and 2 nd degree relatives of carefully phenotyped idiopathic bronchiectasis patients with pulmonary NTM infections, strongly suggesting a genetic component to the disease.…”
Section: Endotypes and Genotypesmentioning
confidence: 99%
“…Some NTM-LD patients have a greater than expected preponderance of abnormalities within the thoracic cage region, such as pectus excavatum and scoliosis [ 46 , 65 , 66 , 67 , 75 , 79 , 80 ]. We and others have postulated that thoracic cage abnormalities may be a marker for an underlying and yet-to-be identified genetic predisposition, perhaps related to a minor variant of Marfan syndrome (due to mutations of fibrillin-1) or ciliary dysfunction (due to mutations of different genes that encode for ciliary proteins) [ 65 , 66 ], [ 75 , 80 , 81 , 82 ]. Pectus excavatum and scoliosis have also been described in other connective tissue disorders, such as Loeys–Dietz syndrome (LDS, due to gain-of-function mutation of transforming growth factor-beta receptors 1/2—TGFβR1/2) and Shprintzen–Goldberg Syndrome (SGS, due to mutation of the Sloan Kettering Institute (SKI) protein, a downstream inhibitor of TGFβ signaling) [ 83 ].…”
Section: Ntm Diseasesmentioning
confidence: 99%
“…In light of this, the whole blood of NTM patients was found to produce more TGFβ, and lower levels of IFNγ upon ex vivo stimulation with various Toll-like receptor agonists or with M. intracellulare as compared to similarly stimulated whole blood from uninfected controls [ 65 ]. Daniels et al analyzed for the presence of dural ectasia—an enlarged dural sac seen in MFS, LDS, and SGS—in patients with idiopathic bronchiectasis, CF subjects, MFS, and controls and found that the L1–L5 dural sac diameter was significantly greater in patients with idiopathic bronchiectasis as compared to controls and to CF subjects, suggesting the possibility of an underlying connective tissue disorder in those with idiopathic bronchiectasis [ 82 ]. They also found a strong correlation between dural sac size and NTM-LD, as well as dural sac size and long fingers [ 82 ].…”
Section: Ntm Diseasesmentioning
confidence: 99%
“…The occurrence of NTM lung disease in individuals without any known predisposing condition is well recognized; a number of these patients possess Marfanoid features such as life-long slender body habitus and thoracic cage abnormalities such as pectus excavatum and scoliosis (50,51,53,(67)(68)(69)(70)(71). We and others have postulated that the aforementioned thoracic cage abnormalities may be a marker for an underlying and yet-to-be identified genetic predisposition, perhaps related to a minor variant of Marfan syndrome or ciliary dysfunction (16,50,51,69,70,(72)(73)(74).…”
Section: Low Body Weight and Susceptibility To Ntmmentioning
confidence: 99%